Mathematical modeling of the initiation and spread of forest firesand their impact on buildings and structures; Вестник Карагандинского университета. Серия Физика; № 3 (99) - Perminov V. A. Valery Afanasievich (2020, 2020)
Currently, methods of mathematical modeling are used to study processes in emergency situations. Forest fires are extremely complex and destructive natural phenomena which depend on availability of fuel, meteorological and other conditions. Mathematical model of forest fire is based on an analysis of known experimental data and using concept and methods from reactive media mechanics. In this paper the theoretical study of the problems of crown forest fire spread in windy condition and their thermal impact on the wooden building were carried out. The research was based on numerical solution of two-dimensional Reynolds equations. The boundary-value problem is solved numerically using the method of splitting according to physical processes. A discrete analogue for the system of equations was obtained by means of the control volume method. A study of forest fire spreading made it possible to obtain a detailed picture of the change of the component concentration of gases and temperature fields in forest fire and on the wall of building with time. It let to determine the limiting distances between forest fire and building for possibility of wooden walls ignition for different meteorology conditions, size of building and intensity of fire impact.